1996
DOI: 10.1111/j.1476-5381.1996.tb16078.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of endothelin receptors in the human umbilical artery and vein

Abstract: 1The aim of the present study was to characterize pharmacologically endothelin receptors that are present in human umbilical vessels. 2 Endothelin-1 (ET-1) and endothelin-2 (ET-2) are potent stimulants of both the human umbilical artery (pEC5o 7.9 and 7.5) and vein (pEC50 8.1 and 8.0). Endothelin-3 (ET-3) is inactive on the artery but contracts the vein (pEC50 7.6). IRL1620 is inactive in both vessels. The order of potency of agonists is suggestive of a typical ETA receptor in the artery (ET-1 = ET-2 > > ET-3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 27 publications
3
20
0
Order By: Relevance
“…Our results are in line with those of Bogoni et al [13] , who found that endothelin-3 induced contraction of endothelium-denuded strip preparations of human umbilical veins. This contraction was inhibited by the selective ETB receptor antagonist BQ-788, but not by the selective ETA receptor antagonist BQ-123.…”
Section: Discussionsupporting
confidence: 83%
“…Our results are in line with those of Bogoni et al [13] , who found that endothelin-3 induced contraction of endothelium-denuded strip preparations of human umbilical veins. This contraction was inhibited by the selective ETB receptor antagonist BQ-788, but not by the selective ETA receptor antagonist BQ-123.…”
Section: Discussionsupporting
confidence: 83%
“…When compared in vessels from the same animals, the potency (pD 2 : 8.4 ± 0.1 and 8.5 ± 0.1, respectively) and the maximal effect (E MAX : 102 ± 5% vs. 99 ± 10%) did not differ significantly between both peptides (Fig. 1A), in line with earlier findings (Bogoni et al, 1996;Saito et al, 1991) and in addition their effects were equally persistent ( Fig. 1D and F).…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, vascular smooth muscle cells in other tissues produce insulin-like growth factor, insulin growth factor binding proteins 3, 4 and 6, platelet-derived growth factor, fibroblast growth factor (Cohick et al 1993;Arnqvist et al 1995;Delafontaine 1995), transforming growth factor-␤ 1 and 2 and activin A (Kanzaki et al 1995), and transforming growth factor-␤ 3 (Stewart et al 1996). Endothelin-1 is predominantly produced by endothelial cells and then binds to specific receptors on vascular smooth muscle cells, which, in fact, have been identified in the human umbilical artery and vein (Bogoni et al 1996). Smooth muscle cells from human microvessels in culture were also shown to produce ET-1 (Anfossi et al 1993).…”
Section: Discussionmentioning
confidence: 99%